Digital Financial Transformation: The Influence of Fintech on The Stability of The Indonesian Financial System - Hasanah, Huswatun; Azansyah, Azansyah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This research examines the influence of financial technology (fintech) on Indonesia's financial system stability using the Error Correction Model (ECM) methodology with monthly data from 2018-2023. The variables used include the bank Z-score as a proxy for financial system stability, and independent variables consisting of e-money ownership, credit cards, ATM cards, P2P lending volume, and a COVID-19 dummy variable, along with control variables for interest rates, inflation, and exchange rates. Using Stata-14 software, data analysis was conducted through a series of tests including unit root tests, cointegration tests, classical assumption tests, and ECM estimation to analyze both short-term and long-term impacts. The research findings reveal that e-money contributes positively to long-term financial stability, while ATM cards and P2P lending demonstrate negative impacts. Interestingly, the COVID-19 pandemic showed positive effects, reflecting the effectiveness of policy responses. These findings provide crucial insights for policymakers in designing regulations that balance innovation and stability in the digital financial era.